GAMBARAN KECEMASAN KELUARGA PENUNGGU PASIEN DI UGD RS PANTI RINI YOGYAKARTA TAHUN 2020 - Permatasari, Indah Sartika; Sudarta, I Wayan; Kristiana , Dorothea Dian; Lero, Eunike Erlita; Wardani, Eunike Rindayu Pradnya Paramitya; Hartanti, Dwi; Sagala, Agus Junianto (Jurnal Kesehatan, 2021)
ABSTRACT An overview of an Aniexty of Patient’s Family in  Emergency Room of Panti Rini Hospital Yogyakarta in June 2020. Background : Anxiety is an uncertain and spreading concern related to feeling of uncertainty and helplessness. The use of the word “Emergency” can effect the fearness and worriness on patient and family. The patient’s family can adapt with the situation dan often ask for the information about the intervention and prognosis. Objective:  To know the level of anxiety in patient’s family in Emergency Room. Research Method :  This was a quantitative research with descriptive non experimental method. The sample was 39  patient’s family taken with non  probability accidental sampling that was started in 08-21 June 2020 in Emergency Room of Panti Rini Hospital Yogyakarta.Result :  The result of this research shows 38 respondents (97,4) experience moderate anxiety in state anxiety, and 33 respondents (84,6 %) experience moderate anxiety in trait anxiety.  Conclusion :  Based on the data analysis in this research, it can be concluded that the level of anxiety in  patient’s family in Emergency Room Panti Rini  Hospital Yogyakarta in June 2020  are most of the 38 respondents (97,4) experienced the moderate anxiety in state anxiety and 33 ( 84,6%) experienced moderate anxiety in trait anxiety. Suggestion: This research can be used as an information about the anxiety of patient’s family in Emergency Room of Panti Rini Hospital Yogyakarta and increase the nursing services as a motivation in giving the service to the patient and family.   Key word: Anxiety, Patient’s family in Emergency Room.